Occupation Through Technology Monopoly : Relationship Between Technology, Globalization and Capitalization - Miko Bangun Agustinus Aritonang; Mark Weeden (Jurnal Ilmu Sosial Mamangan, 2023)
Globalization is made possible first of all by technology, a technology that is decisive and determined by itself. The possibilities that technology offers allow the world to be in a single whole. Globalization is a reality in our daily lives that can be found easily. Globalization is related to economics, technology, and politics. This paper tries to see this relationship with an emphasis on technology. It is the development of technology that has enabled globalization to change the world and all the relationships in it as they are today. Globalization goes well with the liberal political system and the capitalist economic system. This last thing finally makes globalization as an effort to expand the market or in other words globalization becomes a weapon for capitalism to stick and then stick its nails deeper and deeper in the world. Thus, globalization then turns technology, which initially helped create globalization, to turn into "mere" commodities for humans. However, this paper still sees the possibility of changing technology from a commodity to a right for all citizens of the world. Coclusion, when technology is utilized as capital within the framework of capitalism, any new possibilities constantly offered by technology incarnate as new commodities. The novelty of this research is that resistance to IPR can be used as a small example of efforts to fight capitalism which makes technology a commodity creation system.